The Science Diplomacy Digital Index: new ways of measuring science diplomacy—the Lisbon study case in the year of 2021 - Abrantes, Marta; Lacerda, Luís; Mauduit, Jean-Christophe (Frontiers in Political Science, 2025)
Science and technology have extended the diplomatic agenda beyond traditional issues, leading countries to develop networks of science diplomacy. Studying science diplomacy practices in science, technology and innovation hubs can reveal trends, useful for countries planning to establish a future diplomatic presence with a focus on science. Comparing best practices between city hubs can also inform education, research and innovation about international opportunities. This article explores systematically, and for the first time, how countries have been establishing an active presence regarding science diplomacy in Lisbon (Portugal), a city with a flourishing science, technology and innovation ecosystem. More importantly, it uses the Lisbon case study to contribute to the development of a pioneering approach to quantify and compare science diplomacy activities across geographical units by creating a “Science Diplomacy Digital Index” (SDDI), based on content analysis of websites and social media. The top 10 performers of the SDDI in this work include France (index of 78), Germany, Norway and the United States of America (all with 57), Brazil, Finland and Israel (all with 52), China (48), Russia (44), and India (39). By quantifying science diplomacy activities, the SDDI also allows comparisons with other known indices and quantitative measures. For example, a high SDDI score is a common feature between countries with the highest joint publication percentages. A similar correlation can be observed between the SDDI and the S&T component of the Global Soft Power Index. The mapping performed in this work demonstrates the transversal digital publicizing of science diplomacy practices by the diplomatic representations with residency in Lisbon, thus revealing the potential for the creation of networks and/or hubs around this theme in Lisbon, as existent in other cities. While compilation of practices into the SDDI clearly facilitates the reading of efforts of representations by synthesizing complex information, we strongly advise using the index as a starting point for a more in-depth perspective for each representation.